Agave infiernilloensis (sect. Choritepalae, Asparagaceae), a gigantic new species from the Balsas Basin in Western Mexico - Etter, Julia; Kristen, Martin; Rosales-Martínez, C. Santiago; Vázquez-García, J. Antonio (Phytotaxa, 2022)
We describe and illustrate Agave infiernilloensis, a new species of the section Choritepalae (Agavoideae, Asparagaceae). It is morphologically similar to A. gypsicola from which it differs by having larger rosettes and leaves, shorter terminal spine, shorter and recurving inflorescence, more flowers per node, as well as longer flowers, ovary, and filaments. We assessed the species as Endangered (EN) according to the IUCN criteria. We provide a distribution map and a key to the choritepalous species of Agave.